Tornadoes - Schuh, Mari C.; 1975- (Mankato, Minn., 2010)
"Describes tornadoes, how they form, and the tools scientists use to predict them"--Provided by publisher.
Includes bibliographical references (p. 23) and index.
Accelerated Reader AR
Keywords: Tornadoes; Juvenile literature